Fashioning judicial remedies that work in a constitutional society – Establishing a framework for a functional approach to the awarding of constitutional damages in South African law and comparative jurisdictions - Kika, Musa (Department of Public Law, 2020)
The propriety of awarding constitutional damages as appropriate relief in South Africa can be inferred from the discretionary ss 38 and 172(1) of the Constitution which empower the courts to ‘grant appropriate relief’ and to make ‘just and equitable orders’, respectively. These damages are claimable against the State for Bill of Rights infringements as opposed to private individuals or juristic entities. In spite of the remedy’s promise, the jurisprudence of the Constitutional Court (‘CC’) has not been particularly encouraging, with clear guidance on the granting of the remedy still at large. There is a challenge of acceptance of the remedy as part of South African law, and the problem of approach and process. Unsurprisingly, the courts have sought refuge in treading with extreme circumspection, and have approached the remedy in a circumstantial and ad hoc manner. A hybrid and functional approach which is tailor-made and purpose-oriented would help do away with a formalistic approach that has stunted the growth of constitutional damages as a remedy in South African law. This would eliminate elevating form over substance, subordinating constitutional vindication to common law or statutory remedies, and subjecting constitutional rights violations to indirect as opposed to direct constitutional remedy. What must be looked at is the breach that has occurred, the ‘mischief’ that needs to be corrected, and the impact that such correction is intended to have. This would mean that there are instances where constitutional damages would remain appropriate despite the existence of a remedy in common law. This will inevitably involve departing from the archaic approach to remedies, to think in terms of a closed category of ‘tried-and-tested’ remedies. In determining quantum, the comparable common law measure of damages will often be a useful guide, but only to that extent. It is for the courts to make an award which reflects what a court considers to be fair and just under the circumstances. These are the hallmarks of a functional and pragmatic approach that South African courts and those of comparative democracies ought to adopt.